2016
DOI: 10.14202/vetworld.2016.1348-1354
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum sanctum Linn. stimulate the expression of choline acetyltransferase on the human cerebral microvascular endothelial cells

Abstract: Aim:This research was conducted to identify the expression of choline acetyltransferase (ChAT) in human cerebral microvascular endothelial cells (HCMECs) and to clarify the capability of Ocimum sanctum Linn. ethanolic extract to stimulate the presence of ChAT in the aging HCMECs.Materials and Methods:In this study, we perform an in vitro analysis some in the presence of an ethanolic extract of O. sanctum Linn. as a stimulator for the ChAT expression. HCMECs are divided become two groups, the first is in low pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…Kusindarta et al indicated that an ethanolic extract derived from leaves of Ocimum sanctum may stimulate and restores the expression of choline acetyltransferase in ageing human cerebral microvascular endothelial cells and could provide nerve protection and increased production of Ach may enhance the memory and cognitive ability [75]. Scientific studies reveal that the hydroalcoholic extract of Ocimum sanctum exhibits strong antioxidant activity against DPPH and hydroxyl radicals which may be due to the high amount of polyphenols and flavonoids.…”
Section: Ocimum Sanctummentioning
confidence: 99%
“…Kusindarta et al indicated that an ethanolic extract derived from leaves of Ocimum sanctum may stimulate and restores the expression of choline acetyltransferase in ageing human cerebral microvascular endothelial cells and could provide nerve protection and increased production of Ach may enhance the memory and cognitive ability [75]. Scientific studies reveal that the hydroalcoholic extract of Ocimum sanctum exhibits strong antioxidant activity against DPPH and hydroxyl radicals which may be due to the high amount of polyphenols and flavonoids.…”
Section: Ocimum Sanctummentioning
confidence: 99%
“…O. sanctum leaves prepared from Center for Research and Development of Medicinal Plants and Traditional Medicines, Ministry of Health in Tawangmangu, Central Java, Indonesia. Crude extracts and OSE prepared as previously described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The administration of O. sanctum helps to regulated neurotransmitter levels which play an essential role in neuronal function [ 18 ]. On the in vitro studies, OSE was able to maintain the stability of ChAT expression at human cerebral microvascular endothelial cells (HCMECs) mimic young age and restore ChAT expression at mimic old age on in vitro model [ 21 ]. Another evidence stated that OSE exhibits neuroprotective effects against H 2 O 2 induced neuronal cell damage in SH-SY5Y neuronal cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, some manipulation on the intrinsic extracellular matrix by using traditional herb such as Ocimum sanctum extract was already done. In the in vivo and in vitro model using human brain microvascular endothelial cells (HBMECs) which mimics bloodbrain barrier, the treatment of the extract may promote the cell proliferation on the hippocampus area and HBMECs in the condition upregulation of choline acetyltransferase (ChAT) enzyme [11,12]. In addition, there is also a chance to use nanometer-sized scaffolds in the presence of other substrates such as vascular endothelial growth factor or hyaluronic acid with laminin.…”
Section: Tissue Regenerationmentioning
confidence: 99%